2023
DOI: 10.3390/ijerph20043165
|View full text |Cite
|
Sign up to set email alerts
|

The Organization of Outreach Work for Vulnerable Patients in General Practice during COVID-19: Results from the Cross-Sectional PRICOV-19 Study in 38 Countries

Abstract: The COVID-19 pandemic disproportionately affected vulnerable populations’ access to health care. By proactively reaching out to them, general practices attempted to prevent the underutilization of their services. This paper examined the association between practice and country characteristics and the organization of outreach work in general practices during COVID-19. Linear mixed model analyses with practices nested in countries were performed on the data of 4982 practices from 38 countries. A 4-item scale on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…However, practices did not frequently reach out to psychologically vulnerable patients or patients with known problems of domestic violence or issues related to raising or parenting a child. Based on the findings of another PRICOV-19 paper, the Belgian numbers were lower than the European average, except for proactive care for patients with a psychological vulnerability [ 30 ]. Setting up outreach work was one of the new tasks within practices during COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…However, practices did not frequently reach out to psychologically vulnerable patients or patients with known problems of domestic violence or issues related to raising or parenting a child. Based on the findings of another PRICOV-19 paper, the Belgian numbers were lower than the European average, except for proactive care for patients with a psychological vulnerability [ 30 ]. Setting up outreach work was one of the new tasks within practices during COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Having the tools and the lines of communication to identify vulnerable patients and possessing the necessary skills for population management are indispensable prerequisites for success. PRICOV-19 also showed that outreaching was strongly associated with the availability of an administrative assistant, practice manager, or paramedical support staff, thereby stressing the importance of interprofessional practice teams [ 5 , 6 ].…”
Section: Recommendationsmentioning
confidence: 99%
“…Four survey questions regarding outreach initiatives were selected as the outcome variables in the analyses (Table 1). A recent publication of the international PRI-COV-19 consortium regarding the international data on outreach work also used these four items [15]. To determine if these four survey questions captured multiple components related to outreach work, the research team conducted a principal component analysis (PCA) [35].…”
Section: Outcome Measurementioning
confidence: 99%
“…A recent scoping review revealed considerable variability in the conceptualization of outreach work [13]. This paper defines outreach work as proactive, provider-initiated care that goes beyond the typical care provision driven by patient demand [14,15]. Numerous studies have demonstrated the effectiveness of outreach work in promoting continuity of care and providing preventive care for diverse health conditions and demographic groups [14,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%